Application of the Genetic Algorithms (GAs) in determining the optimal transformer tap setting for loss minimization using MATLAB / Mohd Syful Adly Abd. Wahab - Abd. Wahab, Mohd Syful Adly (2003)
This project report presents a new approach to the use of load flow by proposing the incorporation of the Genetic Algorithms (GAs) to search the optimal transformer tap setting in order to minimise the line losses. In this way , the choice of the transformer tap setting can be determined whilst minimising losses and at the same time improved the voltage profile in the power system The performance of this Genetic Algorithms technique was tested using standard IEEE 6-bus system and analysis of results is presented.